2013
DOI: 10.1117/1.jbo.18.11.117009
|View full text |Cite
|
Sign up to set email alerts
|

Optical pen-size reflectometer for monitoring of early dental erosion in native and polished enamels

Abstract: Abstract. Application of the specular reflection intensity was previously reported for the quantification of early dental erosion. Further development of the technique and assembly of the miniaturized pen-size instrument are described. The optical system was adjusted to fit into a handy device which could potentially access different positions in the oral cavity. The assembled instrument could successfully detect early erosion progression in both polished (n ¼ 70) and native (n ¼ 20) human enamels. Different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…In this experiment, we used two parameters to measure enamel erosion: change in surface hardness (ΔSH) and surface reflection intenstiy (rSRI). Previous studies have shown that SRI is a viable additional method to measure the erosive demineralization of permanent enamel [ 37 , 38 , 54 ], because it highly correlates with Knoop surface microhardness, calcium release, and surface roughness [ 36 ]. In the present study, we were able to further demonstrate that SRI is significantly associated with surface hardness measured with Vickers nanoindentations.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we used two parameters to measure enamel erosion: change in surface hardness (ΔSH) and surface reflection intenstiy (rSRI). Previous studies have shown that SRI is a viable additional method to measure the erosive demineralization of permanent enamel [ 37 , 38 , 54 ], because it highly correlates with Knoop surface microhardness, calcium release, and surface roughness [ 36 ]. In the present study, we were able to further demonstrate that SRI is significantly associated with surface hardness measured with Vickers nanoindentations.…”
Section: Discussionmentioning
confidence: 99%
“…A series of in vitro studies have attempted to model early clinical erosion [18,19]. They initially measured 2D roughness change of polished enamel along with other techniques such as calcium analysis and reflectometry.…”
Section: Introductionmentioning
confidence: 99%
“…In their earlier study, Rakhmatullina et al [18] reported that following erosion, polished enamel samples exhibited an increase in diffuse reflection and decrease in spectral reflection, concurrent with a loss in enamel surface microhardness and surface calcium, and suggested a relationship between the increase in diffuse reflection and increase in surface roughness with the progression of erosion. In a follow-up study, using native and polished enamel Rakhmatullina et al [19] reported that the increase in diffuse reflections was related to surface roughness. Other studies have used surface texture measurements to investigate the changes that occur from erosive tooth wear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this method can be used in comparative studies 9 , but the acquired enamel pellicle can influence the results 10 . More recently, the principle of this reflectometer was transferred and adjusted into a portable optical device 11 . This new hand-held reflectometer (Hand-Held) was developed for the purpose of using in the clinical setting and on native enamel surfaces with promising results 11 .…”
mentioning
confidence: 99%
“…More recently, the principle of this reflectometer was transferred and adjusted into a portable optical device 11 . This new hand-held reflectometer (Hand-Held) was developed for the purpose of using in the clinical setting and on native enamel surfaces with promising results 11 . Different to the reflectometer used by Rakhmatullina et al 7 , the miniaturized Hand-Held version has a laser diode source of 635 nm, and the laser beam is coupled into a 105 μm fibre, and the angle of incidence is fixed at ~23°.…”
mentioning
confidence: 99%